College Students' Perceptions of Slut-Shaming Discourse on Campus - Almazan, Vanessa A.; Bain, Steve F. (Research in Higher Education Journal, 2015)
The purpose of this study was to understand the college students' perceptions of slut-shaming discourse. The research indicated that there was a strong correlation between cultural expectations and slut-shaming. According to the results, the perceptions of slut-shaming are influenced by aspects such as: class, culture, media, gender, feminism, ethnicity, religion, and sexuality. Overall, college students were found to be on crossfire of slut-shaming discourse on a college campus. It was concluded, based on the research, the participants have significantly identified with judging a woman by the way she dresses. It is recommended that further research be devoted to slut-shaming perceptions in different: cultures, groups, regions, religions, organizations, media and institutions. Furthermore, counselors will be able to explore efficacious methods of advocacy which are geared more to prevention of SSD (Slut-Shaming Discourse) than just treatment. Creating a multicultural awareness of this adverse social phenomenon will shed light on the subject and encourage more research to be done.
Publisher: Academic and Business Research Institute